Excel 2013 power programming with VBA - Walkenbach, John (Mr. Spreadsheet's bookshelf., 2013)
Maximize your Excel 2013 experience using VBA application development The new Excel 2013 boasts updated features, enhanced power, and new capabilities. Naturally, that means John Walkenbach returns with a new edition of his bestselling VBA Programming book and covers all the methods and tools you need to know in order to program with Excel. With this comprehensive guide, "Mr. Spreadsheet" shows you how to maximize your Excel experience using professional spreadsheet application development tips from his own personal bookshelf. Featuring a complete introduction to Visual Basic for Applications and fully updated for the latest features of Excel 2013, this essential reference includes an analysis of Excel application development and is packed with procedures, tips, and ideas for expanding Excel's capabilities with VBA.-Offers an analysis of Excel application development and a complete introduction to VBA -Features invaluable advice from "Mr. Spreadsheet" himself, bestselling author John Walkenbach, who demonstrates all the techniques you need to create Excel applications, both large and small -Covers navigating the Excel interface, formatting worksheets, interacting with other Office applications, working with collaboration tools, and using sample workbooks and John Walkenbach's award-winning Power Utility Pak to help enhance your Excel skills -Provides tips, tricks, and techniques for expanding Excel's capabilities with VBA that you wont find anywhere else Excel 2013 Power Programming with VBA is packed with procedures, tips, and ideas for achieving Excel excellence with VBA.